Green homes - Brower, Felicia (New York, NY : Children's Press, an imprint of Scholastic Inc., 2024)
"This STEM-based set of True Books introduces students to the engineering innovations that can help us reach more environmentally friendly goals"--
"Envision a brighter future with this STEM-based subset of True Books.Small changes over the years - from smarter light bulbs to energy-efficient appliances - have made our homes more environmentally friendly. In recent years we have learned how to make alternative energies and Earth-friendly building methods and materials a reality. Today we understand how to build green homes - dwellings that have zero negative impact on the environment. Green Homes will show you how.ABOUT THE SERIES:What would a green future look like? Will trains and airplanes be powered by the sun? Will we have homes that have zero impact on the environment? The most pressing challenge facing us today is how to ensure a healthy Earth for ourselves and future generations. This STEM-based set of A True Books introduces students to the engineering innovations that can help us reach those goals. Interesting information is presented in a fun, friendly way - and in the simplest terms possible - and will inspire kids to start envisioning and enacting a more sustainable future"--
Includes bibliographical references (page 45) and index.
Ages 8-10.
Grades 4-6.
Keywords: Ecological houses -- Juvenile literature; Architecture, Domestic -- Environmental aspects -- Juvenile literature; Sustainable architecture -- Juvenile literature